Understanding the Effects of Forage Composition and Structure in Ruminant Nutrition - Kalyn M. Waters; Nicolas DiLorenzo; Graham Cliff Lamb (EDIS)
Approximately 68% of the 16 million square miles of agricultural land worldwide is used for permanent pastures for livestock production. Fortunately, ruminants can convert plant matter that is inedible or of low nutritional value for monogastrics (i.e., swine or poultry) into calorically dense products of high nutritional value. However, the process of converting poor quality plant matter into useful nutrients for ruminants is complex. This 3-page fact sheet provides an overview and understanding of how forage composition and structure affect the nutritive value and nutrient availability to ruminants. Written by Kalyn M. Waters, Nicolas DiLorenzo, and G. Cliff Lamb, and published by the UF Department of Animal Sciences, March 2013.